2009
DOI: 10.1111/j.1744-6163.1991.tb00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Needs of the Schizophrenic Client

Abstract: While a potentially volatile subject, discussion of sex between a nurse and schizophrenic client is a key to improving the patient's overall condition. Despite fears early in the century that schizophrenia caused a breakdown of moral inhibitions, it is now believed that most schizophrenic individuals are very similar, in sexual contexts, to “normal” people. Research shows that schizophrenic men and women are still interested in sexual relations but do not know how to bring their feelings into the open. They al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…Such psychotic manifestations related to sexuality are uncommon and usually disappear after starting antipsychotic medication. 11,14,15 According to Skopec et al 16 most patients with schizophrenia do not differ from controls in terms of actual sexual behavior. On the other hand, relationships of people with serious mental illness are characterized by less intimacy and commitment than in the general population.…”
Section: Schizophrenia and Sexual Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Such psychotic manifestations related to sexuality are uncommon and usually disappear after starting antipsychotic medication. 11,14,15 According to Skopec et al 16 most patients with schizophrenia do not differ from controls in terms of actual sexual behavior. On the other hand, relationships of people with serious mental illness are characterized by less intimacy and commitment than in the general population.…”
Section: Schizophrenia and Sexual Functioningmentioning
confidence: 99%
“…11 Early psychoanalytic theories suggested that psychosis might derive from unconscious homosexual tendencies. 12 Erotic sexual behaviors were also seen as possible causal factors for schizophrenia in pre-schizophrenic patients.…”
Section: Schizophrenia and Sexual Functioningmentioning
confidence: 99%
“…Individuals, in the acute phase of the disorder, have reported experiencing cenesthetic hallucinations of sexual nature, erotomanic delusions, delusions pertaining to sexual identity and hypersexualism (extremely frequent or suddenly increased libido), most of which disappear with the introduction of antipsychotic medications. 11-12 Negative symptoms, like avolition, anhedonia, social withdrawal, etc, are also associated with lack of desire and/or arousal. 13…”
Section: Schizophrenia and Sexuality—an Overviewmentioning
confidence: 99%
“…Individuals, in the acute phase of the disorder, have reported experiencing cenesthetic hallucinations of sexual nature, erotomanic delusions, delusions pertaining to sexual identity and hypersexualism (extremely frequent or suddenly increased libido), most of which disappear with the introduction of antipsychotic medications. [11][12] Negative symptoms, like avolition, anhedonia, social withdrawal, etc, are also associated with lack of desire and/or arousal. 13 Unravelling and identifying the pure influence of the symptoms of schizophrenia on the sexual functionality of the individual is difficult as most patients with schizophrenia take antipsychotic or neuroleptic medicines that also influence sexual activity.…”
Section: Schizophrenia and Sexuality-an Overviewmentioning
confidence: 99%
“…Esta actividad pasa tanto por relaciones heterosexuales y homosexuales (con parejas estables o no) como por masturbaciones. Sin embargo, no todos tendrían una actividad sexual satisfactoria [1][2][3] .…”
Section: Prevalencia Y Peculiaridades De La Actividad Sexual En El Paunclassified